IMPLEMENTASI METODE PROBLEM BASED LEARNING DALAM MATA PELAJARAN MATEMATIKA DI SDI COKROAMINOTO BALIKPAPAN - Rambe, Rafni Juwita; Yusuf, Iskandar (Cahaya Ilmu Bangsa Institute, 2025)
Mathematics is a subject that trains students to think critically, creatively and actively. Even though mathematics plays an important role, many students still find it a difficult subject. This research investigates the application of the Problem Based Learning (problem solving) method in mathematics education at SDI Cokroaminoto Balikpapan in an effort to improve students' mathematical problem solving abilities. This research method adopts a qualitative approach, with data collection techniques in the form of semi-structured interviews and literature study analysis. This Problem Based Learning model hopes that students can develop their critical thinking skills through activities in learning activities, by solving problems Matematika merupakan mata pelajaran yang melatih siswa berpikir kritis, kreatif, dan aktif. Meskipun matematika memiliki peran penting, banyak siswa masih menganggapnya sebagai mata pelajaran yang sulit. Penelitian ini menyelidiki penerapan metode Problem Based Learning (pemecahan masalah) dalam pendidikan matematika di SDI Cokroaminoto Balikpapan dalam upaya meningkatkan kemampuan pemecahan masalah matematika siswa. Metode penelitian ini mengadopsi pendekatan kualitatif, dengan teknik pengumpulan data berupa wawancara semi-terstruktur dan analisis studi pustaka. Model Problem Based Learning ini diharapkan peserta didik dapat mengembangkan kemampuan berpikir kritisnya melalui aktivitas dalam kegiatan pembelajaran, dengan memecahkan masalah